Ticagrelor versus clopidogrel in stent-assisted coil embolization of unruptured intracranial aneurysms. Issue 5 (October 2022) - Chien, Shuo-Chi; Chen, Ching-Chang; Chen, Chun-Ting; Wang, Alvin Yi-Chou; Hsieh, Po-Chuan; Yeap, Mun-Chun; Liu, Zhuo-Hao; Wang, Yu-Chi; Liu, Yu-Tse
Background: Dual antiplatelet therapy is widely used for stent-assisted coil embolization (SACE) for unruptured intracranial aneurysms (UIAs) to prevent thromboembolic events (TEs). Compared to clopidogrel associated with aspirin, knowledge of the safety and efficacy of ticagrelor is lacking in large studies to date. Methods: A retrospective cohort study was conducted from January 2016 to December 2018 with at least one year of follow-up in a single institution and systemic review. Results: Altogether, 153 patients with UIA receiving SACE were separated into two groups: 113 patients receiving clopidogrel plus aspirin and 40 patients receiving ticagrelor plus aspirin. Acute in-stent thrombotic events were noted in two patients in the clopidogrel group (1.77%) and none in the ticagrelor group (0%). Additionally, one patient (0.88%) in the clopidogrel group had an early ischemic stroke (<3 months). Delayed ischemic stroke was noted in 6 patients (5.31%) in the clopidogrel group and 3 patients (7.50%) in the ticagrelor group. There were no major hemorrhagic events in either group. The two groups showed no significant differences with regard to ischemic stroke or hemorrhagic stroke. Conclusion: Compared to the clopidogrel based regimen, ticagrelor can also reduce TEs without increasing bleeding tendency for SACE of UIAs. Ticagrelor combined with low-dose aspirin is a safe and effective alternative option for SACE.